Charging effect of Al2O3 thin films containing Al nanocrystals - Chen, X. B. (2010)
In this work, Al2O3 thin film containing Al nanocrystals (nc-Al) is deposited on Si substrate by radio frequency sputtering to form a metal-insulator-semiconductor structure. Both electron and hole trapping in nc-Al are observed. The charge storage ability of the nc-Al/Al2O3 thin films provides the possibility of memory applications. Charging in the nc-Al also leads to a change in the dc resistance of the thin films, namely, the electron trapping in the nc-Al leads to an increase in the resistance, whereas the resistance is reduced if there is hole trapping in the nc-Al.